Peran Serikat Pekerja Dalam Penguatan Koperasi Karyawan Sebagai Perlindungan Sosial Dan Kesejahteraan Pekerja di PT Steel Center Indonesia - Wiwi Nurochman; Arista Candra Irawati (PMIH Untag Semarang, 2026)
Employee cooperatives represent an important instrument in improving workers’ welfare and supporting the implementation of social protection within the workplace. The effectiveness of employee cooperatives is closely related to the role of labor unions as representatives of workers’ interests in industrial relations. This study aims to analyze the role of labor unions in strengthening employee cooperatives as an instrument of social protection and workers’ welfare at the enterprise level, particularly at PT Steel Center Indonesia. This research applies an empirical juridical approach using a descriptive qualitative method through document study, literature review, and the author’s practical experience in labor union activities within the company. The results indicate that labor unions play an active role in strengthening employee cooperatives through member assistance, increasing workers’ participation in cooperative activities, and monitoring the implementation of collective labor agreements that support the sustainability of employee cooperatives. The involvement of labor unions contributes to strengthening the function of employee cooperatives as a sustainable mechanism of socio-economic protection for workers at the company level.